Difference between revisions of "Forward graininess"

From timescalewiki
Jump to: navigation, search
 
Line 2: Line 2:
 
$$\mu(t) = \sigma(t)-t,$$
 
$$\mu(t) = \sigma(t)-t,$$
 
where $\sigma$ denotes the [[forward jump]] operator.
 
where $\sigma$ denotes the [[forward jump]] operator.
 +
 +
=References=
 +
* {{PaperReference|Functional series on time scales|2008|Dorota Mozyrska|author2=Ewa Pawluszewicz|prev=Backward jump|next=Right scattered}}

Latest revision as of 14:46, 21 October 2017

Let $\mathbb{T}$ be a time scale. The forward graininess function $\mu \colon \mathbb{T}^{\kappa} \rightarrow \mathbb{T}$ is defined by $$\mu(t) = \sigma(t)-t,$$ where $\sigma$ denotes the forward jump operator.

References